Birr al-wālidayn: Studi Komparatif Penafsiran Surah al-Isrā’ 23-24 Perspektif Ibn Kathīr dan M. Quraish Shihab - Fauzi Fathur Rosi; Noer Halimah Asyihabi (Journal of Islamic Scriptures in Non-Arabic Societies, 2024)
In contemporary society, children's neglect in treating their parents properly is increasingly observed. Filial piety, ranking just below the obligation to worship Allah SWT, is essential and extends universally beyond Muslim parents. This research aims to: 1) Analyze the interpretation of Al-Walid according to Ibn Kathīr and M. Quraish Shihab, and 2) Identify differences and similarities in their exegesis of Surah Al-Isra, verses 23-24. Using qualitative library research, primary sources include the tafsir works of Ibn Kathīr and Al-Mishbah by M. Quraish Shihab, along with related journals, articles, and books. Findings reveal: 1) The commandment to worship Allah SWT exclusively, and 2) The obligation for children to show filial piety by avoiding harsh words, even mild expressions like "ah". Children must speak gently and politely, show reverence, pray for their parents, engage in actions that please them, and avoid actions that displease them. This research highlights the importance of maintaining filial piety under all circumstances and practicing iḥsān, treating others better than they treat us. The study compares interpretations by Ibn Kathīr and M. Quraish Shihab, noting a significant distinction in the term hisanan. Ibn Kathīr sees it as a command to do good to one's parents, while Quraish Shihab attributes two meanings: 1) Bestowing favors upon others, and 2) Performing good deeds. The key principle is treating parents with greater kindness and respect than they extend to us.